Analysis of Students’ Errors in Solving Contextual Problems Based on the Learning Style - Wanda Safinatun Najah; Muhammad Jamaluddin (Riemann: Research of Mathematics and Mathematics Education, 2024)
This research is descriptive using a qualitative approach, which has the aim of describing the errors that students have made when solving contextual problems. Error analysis was carried out using Newman's indicators and reviewed based on student learning styles. The research subjects of class VII MTs Miftahul Ulum were three students, the selection of subjects was based on filling out a learning style questionnaire. Data collection methods in this study were written tests, questionnaires, and interviews. Data analysis in this study is data reduction, presenting data, and drawing conclusions. Based on the results of the study, it was found that (i) students with visual learning style showed signs of error in process skills and in writing the final answer (ii) students with auditory learning style showed signs of error in process skills indicators and writing the final answer (iii) students with kinesthetic learning style showed signs of error in understanding indicators, process skills and writing the final answer. The factors that cause students to make mistakes are that students usually make mistakes for two reasons, namely they have minimal knowledge of the material and they rarely practice contextual problems or other problems.